Impact of postoperative complications on outcomes after oesophagectomy for cancer. Issue 1 (29th October 2018) - Goense, L.; Meziani, J.; Ruurda, J. P.; van Hillegersberg, R.
Abstract : Background: To allocate healthcare resources optimally, complication‐related quality initiatives should target complications that have the greatest overall impact on outcomes after surgery. The aim of this study was to identify the most clinically relevant complications after oesophagectomy for cancer in a nationwide cohort study. Methods: Consecutive patients who underwent oesophagectomy for cancer between January 2011 and December 2016 were identified from the Dutch Upper Gastrointestinal Cancer Audit. The adjusted population attributable fraction (PAF) was used to estimate the impact of specific postoperative complications on the clinical outcomes postoperative mortality, reoperation, prolonged hospital stay and readmission to hospital in the study population. The PAF represents the percentage reduction in the frequency of a given outcome (such as death) that would occur in a theoretical scenario where a specific complication (for example anastomotic leakage) was able to be prevented completely in the study population. Results: Some 4096 patients were analysed. Pulmonary complications and anastomotic leakage had the greatest overall impact on postoperative mortality (risk‐adjusted PAF 44·1 and 30·4 per cent respectively), prolonged hospital stay (risk‐adjusted PAF 31·4 and 30·9 per cent) and readmission to hospital (risk‐adjusted PAF 7·3 and 14·7 per cent). Anastomotic leakage had the greatest impact on reoperation (risk‐adjusted PAF 47·1 per cent). In contrast, the impact of other complications on these outcomes was relatively small. Conclusion: Reducing the incidence of pulmonary complications and anastomotic leakage may have the greatest clinical impact on outcomes after oesophagectomy. Abstract : Pulmonary and anastomotic complications matter most